Appointment of Supreme Court Judges in Bangladesh: An Alternative Interpretation of “Consultation” (Dhaka University Law Journal, 2023)
The Supreme Court of Bangladesh in the cases of Manabjamin and Idrisur Rahman held that in the matter of appointment of Judges of the Supreme Court “consultation” with the Chief Justice with primacy of his opinion is a condition of independence of Judiciary. I argue that the appointment of Judges of the Supreme Court by the Executive does not by itself fetter judicial independence provided that the other post-appointment conditions imposed by the Constitution are met. I further argue that Article 98 (appointment of Additional Judges) and Article 99 (permitting Judges to hold ‘judicial’ or ‘quasi-judicial’ offices after retirement) are provisions that compromise with the independence of Judiciary. The Court has never identified these provisions as potential or real threat to the independence of Judiciary. The Court rather over-focused on the mode of appointment as a major aspect of judicial independence. So far as the mode of appointment is concerned, I argue that the accountability of the Executive should be ensured politically and not judicially. This assumes that the whole of the accountability of the Government cannot be claimed to be ensured legally and the vice versa. In his dissent, Joynul Abedin J argued that the mode of appointment of Judges isn’t a component of judicial independence. However, this raises the question: if the Executive disregards the Chief Justice’s opinion, what then? Abedin J didn’t address the Executive’s political accountability in such a scenario. This leaves a gap in our jurisdiction regarding the justifiability of the Executive’s political accountability in Supreme Court Judge appointments. This article aims to fill that void by advocating for political accountability of Executive solely within this context.Dhaka University Law Journal, Vol. 33(1), 2023 P.77-94